1970
DOI: 10.3329/bjvm.v8i1.7399
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Ectoparasitic Infestations in Cattle at Bhawal Forest Area, Gazipur

Abstract: To determine the prevalence of ectoparasitic infestation of cattle in and around the Bhawal forest area in Gazipur district in Bangladesh, an epidemiological investigation was carried out during the period from November 2008 to October 2009. Of 206 cattle examined, 132 (64.07%) were found to be infested with several species of ticks and lice. The prevalence rate was highest in case of Boophilus microplus (45.63%) followed by Rhipicephalus sanguineus (36.89%), Linognathus vituli ((23.30%), Haematopinus euystern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
29
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 12 publications
14
29
3
Order By: Relevance
“…This result is greater than the findings of Magona et al (2015) reported that the prevalence of ectoparasitic infection were showed 1.96% in all clinical cases that was lower than my finding. Rony et al (2010) conducted a study in Gazipur of Bangladesh, and recorded 68.49%, 65.5%, 65.4% and 64.07% prevalence of tick infestation in cattle, respectively which was higher than my result. Ghosh et al (2007) reported 80% cattle affected by ticks in Bangladesh, India and Pakistan.…”
Section: Prevalence Of Bovine Parasitic Diseasesmentioning
confidence: 54%
“…This result is greater than the findings of Magona et al (2015) reported that the prevalence of ectoparasitic infection were showed 1.96% in all clinical cases that was lower than my finding. Rony et al (2010) conducted a study in Gazipur of Bangladesh, and recorded 68.49%, 65.5%, 65.4% and 64.07% prevalence of tick infestation in cattle, respectively which was higher than my result. Ghosh et al (2007) reported 80% cattle affected by ticks in Bangladesh, India and Pakistan.…”
Section: Prevalence Of Bovine Parasitic Diseasesmentioning
confidence: 54%
“…The reason of higher prevalence of tick in livestock species of the study area could be due to the climate and geography of the study area as the climate variables significantly affect ticks distribution in particular region (Estrada-Pena, 2003). Season plays key role in tick propagation and distribution and it is an established that peak tick prevalence has been reported in summer (Rony et al, 2010). From the surrounding part of the study area reports have shown that higher tick prevalence in summer (Durrani and Shakoori, 2009).…”
Section: Ne Usmentioning
confidence: 99%
“…Academic Publishers factors which support tick survival in the specific area including; temperature, humidity, rainfall (Greenfield et al, 2011), vegetation (Gray, 2002), host availability, season (Teel et al, 1996), altitude (Cadenas et al, 2007), breed, age, sex, stage of lactation, gestation period and nutritional status of the animal (Alonso et al, 2007;Yacob et al, 2008), body condition (Rony et al, 2010), method of application of acaricides (Bianchi et al, 2003) and husbandry practices (Sajid et al, 2011), and animal movement (Hassan and Osman, 2003). The reason of higher prevalence of tick in livestock species of the study area could be due to the climate and geography of the study area as the climate variables significantly affect ticks distribution in particular region (Estrada-Pena, 2003).…”
Section: Ne Usmentioning
confidence: 99%
“…In current study, the obtained results showed that Boophilus tick was the only tick species infect cattle, these results were in agreement with Said and Atif (1958) in Shebin El-Kanatir district, Salem (1986) at Sidi Salem district, Darweesh (1999) in Elbehaira Province, El-Kammah et al, (2001) in Giza, Sharkia, Ismailia, El Beheira and Sinai who recorded Boophilus annulatus was found only on cows (100%), Patel et al, (2013) in India and Ramadan et al, (2016) Ramadan et al, (2016) in Qalyobia governorate and disagree with El-Housary (1981) at Kafr El-Sheikh and Ibrahim (1981) in El-Minyia, Rony et al, (2010) in Bangladesh. Mossie et al, (2016) in Ethiopia and Ali et al, (2016) in Pakistan.The difference may be due to use of acaricides and hygienic measures in different localities as well as the immune status of animals.…”
Section: -Discussionmentioning
confidence: 99%